The role of emotion regulation related processes and chronic illness-related shame in depression, anxiety and stress symptoms of people facing coeliac disease - Fernandes, Melanie (2020)
Aim: The current exploratory study sought out to examine the predictive role of emotion regulation related processes (cognitive fusion, experiential avoidance, self-compassion, and self-judgment) and chronic illness-related to shame in the psychopathological symptoms of depression, anxiety and stress in patients presenting a diagnosis of coeliac disease. Method: Sixty-seven participants with self-reported coeliac disease were recruited through a patients’ association and completed an online sociodemographic and clinical questionnaire and a set of self-report instruments, namely the Anxiety, Depression, and Stress Scales – 21 (DASS-21), the Cognitive Fusion Questionnaire – Chronic Illness (CFQ-CI), the Acceptance and Action Questionnaire-II (AAQ-II), the Self-Compassion Scale (SCS), and the Chronic Illness-related Shame Scale (CISS). The mediating role of the emotion regulation related processes and the chronic illness-related shame was analyzed by calculating hierarchical multiple linear regressions. Results: The self-judgment composite index (self-criticism, isolation, and overidentification) was the only significant predictor of depression, anxiety, and stress symptoms in people with coeliac disease. Conclusions: In psychological interventions designed for patients with coeliac disease, assessment and clinical work targeting self-judgment as an emotion regulation process may be relevant to promote therapeutic gains regarding the negative emotional symptoms of depression, anxiety, and stress.